Multi-feature based authentication watermarking scheme for MPEG videos - YE Deng-pan1; SHANG Yue-yun2 (Tongxin xuebao)
In order to more exactly reflect the MPEG video content, a multi-feature based digital signature by fusing the video temporal feature and motion feature and DCT coefficient feature was constructed, which was embedded into videos as watermarking without increasing the complexity of MPEG coding, and a new multi-feature based MPEG video au- thentication scheme was proposed. Experimental results show that the scheme is more robust than the single-feature one to the common processing such as code-switching and recompression, while sensitive to the malicious attacks such as erasure and insertion and replacement. It can further locate the corrupt areas.